New frontiers in ethnography - Hillyard, Sam (Emerald, 2010)
This volume seeks to address continuities and innovations within the ethnographic canon. It uses Hammersley's (1991) book What's wrong with ethnography to open and situate the debate, but then moves to engage with contemporary debates and arguments on both sides of the Atlantic. Today ethnography has matured to become the dominant research paradigm in some sub-disciplines, but it has also been forced to adapt in response to the theoretical challenge of post-structuralism. The book examines in detail the way some more innovative and problematic ways ethnographers have reacted. Throughout, the book seeks to present a critical, realised evaluation of the strength and limitations of ethnography for the future, by celebrating recent innovations, unusual applications or instances of ethnographic practice. Like Hammersley's book in 1991, it faces and challenges fundamental questions regarding ethnographys very contribution to knowledge. The chapters in this volume are designed to appeal to the novice and the experienced ethnographer; for those embarking on ethnographic work for the first time as well as those looking to move into new methodological directions.
Includes index.
Keywords: Social Science -- Research.; Social Science -- Methodology.; Social Science -- General.; Physical anthropology & ethnography.; Social research & statistics.; Ethnology.; elektronické knihy; electronic books